EFFET DE LA TURBULENCE SUR UNE EOLIENNE - DAHOUM, Amina (Université M'sila, 2020)
Le travail présenté porte sur le vent en deux parties. La première partie consiste à proposer un modèle de sillage d’Ishihara qui tient en compte la turbulence liée à l’état du sol et à la présence des obstacles dans un parc éolien. En utilisant les données et les caractéristiques de la turbine GAMESA G52, La deuxième partie se concentre sur l’investigation de l’effet de la turbulence sur la puissance d’une éolienne. Les résultats obtenus ont montrés que ce phénomène influe significativement la puissance développée. Abstract The work presented concerns the wind in two parts. The first part consists in proposing a model of Ishihara's wake that takes into account the turbulence linked to the state of the ground and the presence of obstacles in a wind farm. Using data and characteristics from the GAMESA G52 turbine, Part II focuses on investigating the effect of turbulence on the power of a wind turbine. The results obtained showed that this phenomenon significantly influences the power developed.
Keywords: Modèles de sillage, Énergie éolienne, Turbulence, Ishihara, GAMESA G52.; Wake models, Wind energy, Turbulence, Ishihara. GAMESA G52